1999
DOI: 10.1038/sj.bjc.6690141
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of the topoisomerase II catalytic inhibitor fostriecin

Abstract: SummaryWe conducted a phase I and pharmacokinetic study of the topoisomerase II catalytic inhibitor fostriecin. Fostriecin was administered intravenously over 60 min on days 1-5 at 4-week intervals. Dose was escalated from 2 mg m -2 day -1 to 20 mg m -2 day -1 in 20 patients. Drug pharmacokinetics was analysed with high performance liquid chromatography with UV-detection. Plasma collected during drug administration was tested in vitro for growth inhibition of a teniposide-resistant small-cell lung cancer (SCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 16 publications
(15 reference statements)
1
42
0
1
Order By: Relevance
“…These observations unequivocally demonstrate that the plmS 2 gene product is responsible for catalyzing hydroxylation at C-18 of PLM and is not required for hydroxylation at other positions. Hydroxylation at C-8 and the C-8 ethyl side chain are most likely catalyzed by the second cytochrome P-450 monooxygenase, encoded by plmT 4 . The efficient production of PLM-B by the NP1 strain suggests that hydroxylation at C-18 of PLM-B and the subsequent esterification step may be the final steps in the biosynthetic process.…”
Section: Pcr-targeted Gene Disruption Of Plmsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations unequivocally demonstrate that the plmS 2 gene product is responsible for catalyzing hydroxylation at C-18 of PLM and is not required for hydroxylation at other positions. Hydroxylation at C-8 and the C-8 ethyl side chain are most likely catalyzed by the second cytochrome P-450 monooxygenase, encoded by plmT 4 . The efficient production of PLM-B by the NP1 strain suggests that hydroxylation at C-18 of PLM-B and the subsequent esterification step may be the final steps in the biosynthetic process.…”
Section: Pcr-targeted Gene Disruption Of Plmsmentioning
confidence: 99%
“…2 -Analysis of the PLM biosynthetic gene cluster, together with the results of the biosynthetic incorporation study, indicated that three hydroxylation steps (C-18, C-8, and the C-8 ethyl side chain) occur after assembly of the polyketide chain from the CHC-derived starter unit. Analysis of the PLM biosynthetic gene cluster revealed two ORFs, plmT 4 and plmS 2 , that both encode proteins with high sequence similarity to each other (38% identity and 53% similarity) as well as cytochrome P-450 monooxygenases from several microorganisms, including those involved in the modification of the natural products of streptomycetes (41). We reasoned that replacement of one of these genes would provide a strain blocked in hydroxylation of C-18 of PLM.…”
Section: Incorporation Studies Establish Chc As a Precursor To Allmentioning
confidence: 99%
See 1 more Smart Citation
“…曲 星 (Fostriecin) [1,2] 、 哥 纳 香 甲 素 (Goniothalamin) [3] 、 Cytostatin [2] 、Leptomicin B [4] 、Anguinomycin [2] 、Piro- Micheal 加成, 形成共价键 [4,8] , 在发挥作用的同时, 也 …”
Section: αβ-不饱和-δ-内酯是一类重要的天然产物 如福司unclassified
“…8 Fostriecin demonstrated sufficient antitumor activity in animals to warrant Phase I human clinical trials. 9,10 The other afore-mentioned natural products are strong inhibitors (IC 50 ; low nM) of PP1/PP2A/PP4/PP5/PP6 that demonstrate modest or no selectivity. They have some utility as research reagents, but the combined inhibition of PP1-PP6 is toxic to most, if not all, eukaryotic cells.…”
Section: Introductionmentioning
confidence: 99%